PENGARUH KEMAMPUAN MEMBACA AL-QUR’AN TERHADAP MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN AL-QUR’AN HADITS KELAS VII E DI MTs 2 KUANTAN SINGINGI - Upipa Aselta; Andrizal Andrizal; Alhairi Alhairi (Universitas Islam Kuantan Singingi, 2023)
The ability to read the Qur'an is a learning result obtained by students as a change caused by learning activities. This then affects their learning motivation, both to improve and maintain their learning outcomes. In the pre-study at MTs Negeri 2 Kuantan Singingi in class VII E, it was found that the students' ability to read the Qur'an could be said to be good because it could be seen from their practice scores which were above the KKM. However, the students' learning motivation in the class cannot be said to be good because it seems that there are some who are less active in the learning process, show an unconfident attitude, and some are doing activities outside the learning context during the learning process. So this study aims to find out whether there is an effect of the ability to read the Qur'an on students' learning motivation in the subjects of Al-Qur'an Hadith Class VII E at MTs Negeri 2 Kuantan Singingi. This type of research is quantitative with a research sample of 27 people. The primary data collection techniques used are questionnaires and tests. The results showed that there was no effect of the ability to read the Qur'an on students' learning motivation based on the results of a simple linear regression analysis where the Significance Value (Sig.) 0.285 > Probability 0.05. Similarly, the T-test where t-count -1.093 < t-table 2.060